serve
serve 24 b of the wind, tide - be favourable 54 to bind a rope with small cord (Naut) 47 To treat in a specified (usually unpleasant or unfair) manner - chiefly _colloquial_ - withdraw? Agreed [check] G withdraw? withdraw? Not used Not used Withdrawn